A REVIEW ON THE SOCIOECONOMIC DETERMINANTS OF LIVING WAGE DURING COVID-19 PANDEMIC - Siti Hajar Samsu; Lim Fui Yee Beatrice; Khairul Hanim Pazim; Dayangku Aslinah Abd Rahim; Roslinah Mahmud (Journal of Islamic, Social, Economics and Development, 2022)
As Malaysia moves closer to being a high-income country, all residents should strivefor a minimum acceptable quality of living. Households are finding it harder to maintain asufficient quality of living as the cost of living rises. The purpose of this study is to reviewliterature on the socioeconomic determinants of the living wage particularly pre,during andpost Covid-19 Pandemic. A household, in this context, refers to an individual or a group ofindividuals who live together in the same house and make economic decisions collectively,whether related or not. This study used the library research method to collect and analyse thedata. We outline the drivers of living wage and analyse the links that exist between living wageand socioeconomic variables arising from the literature, which focuses on empirical works.According to earlier study, housing costs, food costs, transportation costs, communicationcosts, healthcare costs, education costs, household size, number of full-time jobs, and savingsare all key determinants, notably pre, during and post the Covid-19 Pandemic.